Popliteal Venous Aneurysm Presenting With Bilateral Pulmonary Thromboembolism. (May 2018) - Ghali, Michael George Zaki; Taylor, Jesse A.; Mallon, Mary; Gerety, Patrick; Shea, Paul; Weinberger, Sharon; Urbine, Jacqueline; Raybagkar, Deepti
A 12-year-old boy presenting with chest pain and dyspnea was found to have bilateral pulmonary thromboembolism (PTE) secondary to left popliteal venous aneurysm (PVA) with thrombus. He improved with thrombolytics, developed recurrent PTE, then underwent surgical repair of his PVA. The pathophysiology, diagnosis, and management of PVA are discussed.